ANALISIS KESULITAN SISWA DALAM MEMAHAMI READING DAN STRUCTURE PADA PEMBELAJARAN BAHASA INGGRIS DI SMP N 1 RANAH PESISIR - Yani, Titik Hardewi; Melshandika, Yola; Veni, Veni (STKIP Pesisir Selatan, 2021)
This research started from researcher’ observation on English students’ ability that still low at seventh grade SMP N 1 Ranah Pesisir, and students’ opinion of English is bored and difficult. Based on the problems, this research purpose was to analyze students’ difficulties in understanding English learning, especially Reading Comprehension and Structure. The research method was descriptive qualitative. The research sampling was seventh grade students at SMPN 1 RanahPesisir, in choosing the sample was used purposive sampling technique. It was done because its class had mean score which low than others. More than 50 % of students got score under Minimum Completeness criteria. To get the data, the researcher had done interview for the students and English teacher, then done observation and document that were gotten the score of reading and structure material. From the result research were gotten that reading and structure understanding at seventh grade students SMP N 1 Ranah Pesisir, low. 40% from 25 students were difficulties in understanding them. The students difficulties of reading and structure understanding was caused less students’ concentration in learning, students’ learning habit which mistake, and students’ bored in English learning, beside teacher rarely did correction on students’ task.